Profil Penggunaan Obat Antihipertensi Pada Pasien Rawat Inap di RSUD La Temmamala Kabupaten Soppeng - Nugraha, Akram Resa; Herman, Hendra; Purnamasari, Vina (PHARMACY UMI JOURNAL SYSTEM, 2024)
Hypertension has become one of the deadly diseases in both Indonesia and the world. Hypertension (or high blood pressure) is defined as a condition when the blood pressure is above 140/90 mmHg. According to the profile of the Health Department of South Sulawesi Province in 2018, Soppeng Regency has the highest rate of people with hypertension at 98,79% with 4.997 from 5.058 patients. The purpose of this research is to describe the usage of anti-hypertension medicines to the patients at Latemmalala Regional Public Hospital, Soppeng Regency, in the period between June-December 2022. This research is considered a quantitative research with the descriptive method and observational research design, as well as the retrospective approach that begins with the documentary research taken from the patient’s medical records. The result shows that the characteristic rate of the patients according to the gender is mostly found on females, with 20 patients being confirmed (67,5%), for the ages between 60-69 years old, 15 patients are confirmed (46,9%), and the following disease that is also found on the patients with hypertension is the kidney failure, where there are 14 patients being confirmed (20%). The most used type of medicine is the calcium channel blocker (CCB), another medicine that is also often used is the 57 units of amlodiphine (37,5%), and the most-used combined medicines are 9 units of amlodiphine and furosemid (39,1%). According to the accuracy and the inaccuracy of the medical usage, the accuracy is 100% and the inaccuracy is 0%.